2021
DOI: 10.1007/s13399-021-01971-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tensile strength of PLA/clay/rice husk composites using Box-Behnken design

Abstract: It is extremely important to save costs and time while enhancing accuracy in experimentation. However, no study has utilized response surface methodology (RSM) to obtain the effects of independent parameters on properties of PLA/clay/rice husk composites. This study focused on optimization of tensile strength of fiber-reinforced polylactic acid (PLA) composites. RSM using Box-Behnken design (BBD) was used to determine optimum blending parameters of the developed composites. Fiber-reinforced PLA composites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Also, nanocomposites of PLA with untreated rice husk at 4 and 6% [ 50 ] were made by an electrospun process, and although strength is reported to be doubled with respect to the neat sample, the results are not clearly presented. Other authors showed that combining PLA with rice husk 10–30% and clay 1–5% can increase tensile strength up to 33 MPa, although compression molding was used [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, nanocomposites of PLA with untreated rice husk at 4 and 6% [ 50 ] were made by an electrospun process, and although strength is reported to be doubled with respect to the neat sample, the results are not clearly presented. Other authors showed that combining PLA with rice husk 10–30% and clay 1–5% can increase tensile strength up to 33 MPa, although compression molding was used [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While although researchers have done a large number of studies on plant fiber filled PLA composites, there are few studies focus on the thermal decomposition characteristics of 3D printed MNRH/PLA composites. [24][25][26] Costa et al investigated the thermal stability of pinecone residue toughened with acrylonitrile-butadiene-styrene (ABS) for 3D printing pens, and evaluated the thermogravimetric analysis of ABS, FR, FT, FB, and their filament composites. Results demonstrate that the first process from room temperature to 130°C is attributed to water evaporation, while the second process is related to the degradation of hemicellulose, lignin, and cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] It has been already reported that adding a small amount of inorganic layered silicate as a filler modifier into the PLA matrix can not only improve the crystallization rate of PLA and enhance the crystallization performance of PLA, but also can improve the crystallization rate of PLA. [21,22] Besides, fillers such as clays [23] can enhance the comprehensive properties of polylactic acid materials. However, fillers able to act as chain extenders have been rarely reported so far.…”
Section: Introductionmentioning
confidence: 99%